Organizational Change - Pathak, Harsh (Pearson India, 2012)
Business is changing at a break-neck speed, so managers must be increasingly active in reorganizing their firms to gain a competitive edge. This textbook provides a discussion of change in relation to the complexities of organizational life, offering comprehensive coverage of the significant ideas and issues associated with change at all levels of organizational activity from the strategic to the operational and at the individual, group, organizational and societal levels. Taking both a theoretical and a practical approach to the issues of organizational change, the text seeks to meet both the academic and applied aims of most business and management courses. The book is ideal for both MBA students and those studying for the more specialist degrees in organizational change. Its structure and content also make it accessible to final-level undergraduate business studies students